Antibiotic Prescribing at the Transition from Hospitalization to Discharge: A Target for Antibiotic Stewardship. (20th January 2015) - Yogo, Norihiro; Haas, Michelle K.; Knepper, Bryan C.; Burman, William J.; Mehler, Philip S.; Jenkins, Timothy C.
Abstract : Of 300 patients prescribed oral antibiotics at the time of hospital discharge, urinary tract infection, community-acquired pneumonia, and skin infections accounted for 181 of the treatment indications (60%). Half of the prescriptions were antibiotics with broad Gram-negative activity. Discharge prescriptions were inappropriate in 79 of 150 cases reviewed (53%). Infect Control Hosp Epidemiol 2015;00(0): 1–5